Dynamics of homocysteine precursors and methylation index in high-class biathletes at the stages of the preparatory period of the annual cycle - Dikunets M.A.,; Dudko G.A.,; Viryus E.D.,; Fedotova E.V., (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the dynamics of S-adenosylmethionine, S-adenosylhomocysteine ​​and methylation index in high-class biathletes at the stages of the preparatory period of the annual cycle. Methods and structure of the study. Participants in the experiment are athletes of the Russian national biathlon team (n=23). Quantitative analysis of homocysteine ​​precursors in blood samples of study participants was performed on an ultrafast liquid chromatography-mass spectrometer with triple quadrupole LCMS-8060 (Shimadzu, Japan). Results and conclusions. The features of the dynamics of the concentrations of homocysteine ​​precursors and the methylation index were studied within the preparatory period of the annual cycle of high-class biathletes. At the stages of the preparatory period of different orientation, intensity and specificity of the preparation means used, the frequency of occurrence of cases of a reduced level of the methylation index was revealed: at the general preparatory stage – 14,52%, at the special preparatory stage – 32,26%, at the pre-competition stage – 5,00%. It was established that the decrease in the methylation index during the training period under consideration is due to a shift in the direction of training loads towards high-intensity motor modes.